Electromagnetic theory of microstretch elasticity and bone modeling - Eringen, A.Cemal (International journal of engineering science, 2004)
A continuum theory of microstretch elasticity subject to electromagnetic fields is introduced as a microstructural model to determine deformations and stress fields in elastic solids having interconnected voids, microcracks or stretchable microelements. Such materials include animal bones and solids with deformable microstructures, e.g., nanocomposites in solids.